2006
DOI: 10.1021/ie0600691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Feed Stream and Agitator Type on CFSTR Mixing State

Abstract: The hydrodynamics of a continuous-flow stirred tank reactor (CFSTR) have been studied through RTD measurements, visual tracing, and CFD simulations, for an axial-flow and two radial-flow impellers (Mixel TT and Rushton and NS turbines), to investigate how the combination of impeller choice and operating conditions (flow rates, agitator speed) affect the vessel hydrodynamics and flow nonideality. The portion of the total vessel volume being perfectly mixed decreases considerably as the vessel utilization is for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Such studies reported in literature are mainly based on ideal CSTRs. Few publications addressed effect of non-ideal flows on mixing performance due to various design and process variables (Samaras et al, 2006). This is mainly due to the lack of an effective method of study.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies reported in literature are mainly based on ideal CSTRs. Few publications addressed effect of non-ideal flows on mixing performance due to various design and process variables (Samaras et al, 2006). This is mainly due to the lack of an effective method of study.…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of the inlet and outlet EPJ Web of Conferences [2] solenoid valve, [3] tracer tank, [4] metering pump, [5] progressing cavity pump, [6] conductivity sensor, [7] data acquisition system, [8] electric motor, [9] torque meter, [10] mixing tank, and [11] discharge tank. pipes was 0.025 m. The mixing tank was equipped with a top-entering impeller driven by a 2-hp motor.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…These non-ideal flows should be avoided as they decrease the efficiency of the mixing system. Although several studies have been done on the continuous-flow mixing of Newtonian fluids [8][9][10][11]; there is little information available in the literature on the continuous-flow mixing of non-Newtonian fluids. Thus, it is imperative to study the dynamic behavior of continuous-flow mixing under realistic mixing conditions since ignoring non-ideal flows can lead to errors in the system design [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to diagnose abnormalities in flow in the continuous-flow reactors because of a noteworthy effect of mixing efficiency on the product quality (Paul et al, 2004). The non-ideal flows have been identified by some researchers in the continuous-flow mixing of Newtonian-fluids in stirred vessels using CFD (Aubin et al, 2006;Khopkar et al, 2004), residence time distribution (Samaras et al, 2006), laser Doppler velocimetry (LDV) (Mavros et al, 1997(Mavros et al, , 2002a(Mavros et al, , 2002b and spectrophotometer (Roussinova and Kresta, 2008 tests (Ein-Mozaffari et al, 2003Patel et al, 2011Patel et al, , 2012aPatel et al, , 2012b, tomography (Patel et al, 2013a(Patel et al, , 2013b(Patel et al, , 2014a(Patel et al, , 2014b, CFD Ford et al, 2006;Fathi Roudsari et al, 2013), and residence time distribution (Jones et al, 2009). CFD is an effective tool for investigating the fluid flows in mixing systems and can be easily employed to obtain the mixing data that cannot be simply measured through the experimental tests.…”
Section: Introductionmentioning
confidence: 99%